Augmentative and Alternative Communication for Children with Intellectual and Developmental Disability: A Mega-Review of the Literature - Crowe, Becky (J Dev Phys Disabil, 2021)
Establishing evidence- and research-based practices relies upon research synthesis of individual studies in reviews and meta analyses. Further summarizing scientific evidence about a specific topic by synthesizing reviews is an area of need to determine practices that have a strong evidence base and to identify areas of methodological weakness and gaps in the literature. A mega-review of literature reviews, systematic reviews, and meta-analyses on interventions using aided augmentative and alternative communication (AAC) interventions for children with intellectual and developmental disabilities from 2000 to mid-2020 was conducted. Participant and interventionist demographics, interventions, settings, outcomes, and recommendations of each review were reported and summarized. A MeaSurement Tool to Assess systematic Reviews Revised (AMSTAR 2; Shea et al., 2017) was used to examine the methodological rigor of 84 included reviews. Over the past 20 years, published reviews have increased slightly in methodological rigor but demonstrate a number of methodological weaknesses that detract from the strength of evidence for AAC interventions with this population. Suggestions for improving the methodological rigor of literature reviews and areas for future research specific to AAC interventions are discussed.